Efektivitas blended learning untuk meningkatkan keterampilan membaca di MTS Al Munawaroh Jombang - Zaini Hariri Shofa; Siti Durotun Naseha (JOURNAL SAINS STUDENT RESEARCH, 2025)
The ability to read in Arabic is important for understanding the language and improving speaking and writing skills. The use of technology-based learning such as blended learning that combines traditional and digital methods is considered capable of increasing learning effectiveness and providing flexibility according to student needs, especially in the industrial era 4.0. This study aims to determine the effectiveness of blended learning in improving reading skills and its success factors at MTs Al-Munawaroh. With a single group pretest-posttest design experimental quantitative approach, the researcher tested 20 seventh grade students using valid instruments that were analyzed through a T-test in SPSS. The results showed an increase in the mean score from 81.60 to 91.80 which was statistically significant. The implementation of blended learning was done through the presentation of learning videos, structured testing, and the use of digital devices that support interactivity and learning independence. Despite the limitations, the results of this study confirm the effectiveness of blended learning and the importance of developing this model to be applied more widely in the future.